Thromboelastometry (ROTEM®) in children: age-related reference ranges and correlations with standard coagulation tests - Oswald, E; Stalzer, B; Heitz, E; Weiss, M; Schmugge, M; Strasak, A; Innerhofer, P; Haas, T (British journal of anaesthesia : BJA, 2010)
The small sample volume needed and the prompt availability of results make viscoelastic methods like rotational thromboelastometry (ROTEM®) attractive for monitoring coagulation in small children. However, data on reference ranges for ROTEM® parameters in children are scarce. Four hundred and seven children (ASA I and II) undergoing elective surgery were recruited for this prospective, two-centre, observational study. Subjects were grouped as follows: 0–3, 4–12, 13–24 months, 2–5, 6–10, and 11–16 yr. Study objectives were to establish age-dependent reference ranges for ROTEM® assays, analyse age dependence of parameters, and compare ROTEM® data with standard coagulation tests. Data from 359 subjects remained for final analysis. Except for extrinsically activated clot strength and lysis, parameters for ROTEM® assays were significantly different among all age groups. The most striking finding was that subjects aged 0–3 months exhibited accelerated initiation (ExTEM coagulation time: median 48 s, Q1–Q3 38–65 s; P=0.001) and propagation of coagulation (α angle: median 78o, Q1–Q3 69–84o; P<0.001) and maximum clot firmness (median 62 mm, Q1–Q3 54–74 mm), although standard plasma coagulation test results were prolonged (prothrombin time: median 13.2 s, Q1–Q3 12.6–13.6 s; activated partial thromboplastin time: median 42 s, Q1–Q3 40–46 s). Lysis indices of <85% were observed in nearly one-third of all children without increased bleeding tendency. Platelet count and fibrinogen levels correlated significantly with clot strength, and fibrinogen levels correlated with fibrin polymerization. Reference ranges for ROTEM® assays were determined for all paediatric age groups. These values will be helpful when monitoring paediatric patients and in studies of perioperative coagulation in children.